Generation of Nicotinic Acid Adenine Dinucleotide Phosphate and Cyclic ADP-Ribose by Glucagon-Like Peptide-1 Evokes Ca2+ Signal That Is Essential for Insulin Secretion in Mouse Pancreatic Islets - Byung-Ju Kim; Kwang-Hyun Park; Chang-Yeol Yim; Shin Takasawa; Hiroshi Okamoto; Mie-Jae Im; Uh‐Hyun Kim (2008)
Glucagon-like peptide-1 (GLP-1) increases intracellular Ca(2+) concentrations ([Ca(2+)](i)), resulting in insulin secretion from pancreatic beta-cells. The molecular mechanism(s) of the GLP-1-mediated regulation of [Ca(2+)](i) was investigated.GLP-1-induced changes in [Ca(2+)](i) were measured in beta-cells isolated from Cd38(+/+) and Cd38(-/-) mice. Calcium-mobilizing second messengers were identified by measuring levels of nicotinic acid adenine dinucleotide phosphate (NAADP) and cyclic ADP-ribose (ADPR), using a cyclic enzymatic assay. To locate NAADP- and cyclic ADPR-producing enzyme(s), cellular organelles were separated using the sucrose gradient method.A GLP-1-induced [Ca(2+)](i) increase showed a cooperative Ca(2+) signal, i.e., an initial [Ca(2+)](i) rise mediated by the action of NAADP that was produced in acidic organelles and a subsequent long-lasting increase of [Ca(2+)](i) by the action of cyclic ADPR that was produced in plasma membranes and secretory granules. GLP-1 sequentially stimulated production of NAADP and cyclic ADPR in the organelles through protein kinase A and cAMP-regulated guanine nucleotide exchange factor II. Furthermore, the results showed that NAADP production from acidic organelles governed overall Ca(2+) signals, including insulin secretion by GLP-1, and that in addition to CD38, enzymes capable of synthesizing NAADP and/or cyclic ADPR were present in beta-cells. These observations were supported by the study with Cd38(-/-) beta-cells, demonstrating production of NAADP, cyclic ADPR, and Ca(2+) signal with normal insulin secretion stimulated by GLP-1.Our findings demonstrate that the GLP-1-mediated Ca(2+) signal for insulin secretion in pancreatic beta-cells is a cooperative action of NAADP and cyclic ADPR spatiotemporally formed by multiple enzymes.